KONFERENSI PEMUDA BALI 2024: PENGUATAN MODERASI BERAGAMA MELALUI PARTISIPASI PEMUDA DALAM ISU PUBLIK - Ni Nyoman Yunike Kurniarini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The value of religious moderation plays an important role in maintaining harmony in multicultural life which is very close to conflict due to differences. The value of religious moderation takes a middle path to the strong pluralism bias in society. Nowadays, strengthening the value of religious moderation is one of the main targets in government work programs, especially at the Ministry of Religion. The internalization of the value of religious moderation is not only starting to be included in the educational curriculum but is also being structured in the general public, for example through activities related to public issues. One of these activities is the Bali Youth Conference which was initiated by the BasaBali Wiki Foundation to increase community participation, especially millennials, in responding to public issues in society, including issues of tolerance and diversity. This research aims to describe strengthening the value of religious moderation through youth participation in solving public issues. The methods used in this research are observation, interviews, and document analysis. The results obtained are the youth's understanding of forming a pathway for solving public issues in society, including issues of pluralism. Keywords: Religious Moderation, Public Participation, Public Issue, Bali Youth Conference